Metamorphosis of workforce management: The implication on employee retention towards sustainable development - Adesanyan, Abel Segun; Ojodu, Hammed Omotola; Adeyeye, Victor A; Eniayewu, Jamiu Abiola (Papanda Publishier, 2025)
This paper tends to offer an insight into workforce management in its various forms and developmental stages. It also seeks to bring to light the Millennials or Generation Y who seem to be the most relevant workforce in today’s organization. While highlighting the relevance of the Gen Y(s), this work also looks at the retention strategies that will keep this generation happy and stable in the workplace to ensure efficient productivity and profitability. The retention strategies come into strong focus because this will go a long way in ensuring the stability of organizations in the present economic circumstances and concluded that understanding the generation of one’s employees will enhance employee retention in the workplace.